A new genus and species of troglobitic ground beetle from eastern Guizhou, Southwest China (Coleoptera: Carabidae: Trechinae) - Zhao, Danyang; Tian, Mingyi (Zootaxa, 2016)
Tianzhuaphaenops jinshanensis n. gen., n. sp. is described from a limestone cave called Jinshan Rongdong in the easternmost Guizhou Province of Southwest China. This troglobitic trechine genus is related to Guizhaphaenops- Qianotrechus- Qianaphaenops complex but its precise position remains undetermined.